Thin liquid polymer films rupture via defects - Mecke, Klaus; et al. (Langmuir, 1998)
The standard rupture scenario of thin polymer films on solid substrates is investigated in detail. The geometry of the dewetting structure is analyzed by means of the Minkowski functionals in two dimensions. Furthermore, the temporal behavior and the impact of ambient conditions are considered. In contrast to what has been frequently asserted, we show that spinodal dewetting does very probably not play any significant role in the rupture process. On the contrary, it is demonstrated that rupture is dominated by nucleation from defects, which are intrinsic to the polymer due to its peculiar morphology. It is concluded that polymer films on solid surfaces are either stable (in the case of complete wetting) or unstable, but never metastable.